Cola beverage reduces risk of lead poisoning from accidental ingestion of contaminated soil particles in rat and swine models - Xiaoyun Xu; Quan Qian; Yao Shi; Wenfeng Huang; Chengpeng Yuan; Lena Q. Ma; Willie G. Harris; Jiayin Dai; Deyi Hou; Xinde Cao (Nature Communications)
Abstract Accidental ingestion of lead (Pb)-contaminated soils represents a major route of Pb exposure for both adults and children, and the development of accessible and cost-effective solutions to reduce Pb poisoning is urgently required. Here, we present an effective and straightforward technique, involving the consumption of cola beverages, for the purpose of lowering blood Pb levels following the ingestion of contaminated soils in animal models. This method facilitated the direct passage of Pb in contaminated soil through the digestive system, enhancing its elimination without absorption into systemic circulation. Our results demonstrated that cola effectively reduced Pb bioaccessibility in 22 contaminated soils by 32.6%–98.8%. In male rats and swine exposed to Pb-contaminated soils, cola treatment decreased blood Pb concentrations by 32.9%–96.0% and 31.5%–81.5%, respectively. This cola-induced reduction in Pb bioaccessibility and bioavailability was attributed to the rich phosphoric acid content in cola, which promoted the formation of insoluble Pb phosphate precipitate (pyromorphite [Pb5(PO4)3Cl]) during the gastric phase. The precipitate was directly excreted in feces, resulting in lower Pb absorption in the blood. These findings suggest that the consumption of cola beverages may be a practical strategy to mitigate the risk of Pb poisoning following the accidental ingestion of contaminated soils. However, the applicability of this approach in humans remains uncertain in the absence of population-based studies. While these findings underscore the potential for cola beverages to reduce Pb absorption following soil ingestion in animal models, further research is necessary to evaluate its safety, efficacy, and possible risks in humans before any such protocols are initiated.